Unlocking Agility: An Insider's Guide to Agile Enterprise Transformati on - Hesselberg, Jorgen (Addison-Wesley Professional, 2018)
Today’s enterprises see smaller, more nimble competitors devouring the ir businesses and obsoleting their markets at an ever-accelerating pac e. “Sustainable” competitive advantages continue to shrink and disappe ar, as the average age of Fortune® 500 companies keeps declining. Smar t executives know they must move from plan-driven, fixed-scope thinkin g to a discovery-driven approach characterized by learning, continuous improvement, and value delivery. They know they must learn how to cap italize on uncertainty, since it’s now utterly impossible to prevent i t. Yet, very few large enterprises have truly succeeded in this agile transformation. Unlocking Agility: An Insider’s Guide to Agile Enterpr ise Transformation focuses on overcoming the real challenges that stan d in their way.Author Jorgen Hesselberg has spent 15+ years leading su ccessful enterprise transformation initiatives: this book brings toget her all he’s learned about what works (and what doesn’t). Hesselberg a nswers crucial questions like: What’s the best way to start organizati onal change in large organizations? How can you sustain momentum beyon d the initial “honeymoon”? How do you create an environment of continu ous learning, employee empowerment, and product discovery – while stil l executing superbly in day-to-day customer commitments? What’s the be st role for external consultants and consulting firms? How do you lead coherent organizational change across multiple geographies, locations , and cultures? What organizational structures are likeliest to unlock lasting change, and how should these evolve over time? What type of o rganizational impact is realistic to expect? How can you measure succe ss? Replete with first-hand accounts from transformation leaders at co mpanies including Cisco, HP, Spotify, Yahoo!, John Deere, Salesforce a nd Wal-Mart, the book provides indispensable practical insights for ev eryone seeking to build a truly agile enterprise.